Different microRNA alterations contribute to diverse outcomes following EV71 and CA16 infections: Insights from high-throughput sequencing in rhesus monkey peripheral blood mononuclear cells. (December 2016) - Hu, Yajie; Song, Jie; Liu, Longding; Li, Jing; Tang, Beibei; Wang, Jingjing; Zhang, Xiaolong; Zhang, Ying; Wang, Lichun; Liao, Yun; He, Zhanlong; Li, Qihan
Abstract: Enterovirus 71 (EV71) and Coxsackievirus A16 (CA16) are the predominant pathogens of hand, foot, and mouth disease (HFMD). Although these viruses exhibit genetic homology, the clinical manifestations caused by the two viruses have some discrepancies. In addition, the underlying mechanisms leading to these differences remain unclear. microRNAs (miRNAs) participate in numerous biological or pathological processes, including host responses to viral infections. Here, we focused on differences in miRNA expression patterns in rhesus monkey peripheral blood mononuclear cells (PBMCs) infected with EV71 and CA16 at various time points using high-throughput sequencing. The results demonstrated that 106 known and 13 novel miRNAs exhibited significant differences, and 32 key miRNAs among them for target prediction presented opposite trends in the EV71- and CA16-infected samples. GO and pathway analysis of the predicted targets showed enrichment in 14 biological processes, 10 molecular functions, 8 cellular components and 104 pathways. Subsequently, regulatory networks of miRNA-transcription factors, miRNA-predicted targets, miRNA-GOs and miRNA-pathways were constructed to reveal the complex regulatory mechanisms of miRNAs during the infection phase. Ultimately, we analysed hierarchical GO categories of the predicted targets involved in immune system processes, which indicated that the innate and adaptive immunity following EV71 and CA16 infections may be remarkably distinct. In conclusion, this report is the first describing miRNA expression profiles in PBMCs with EV71 and CA16 infections using high-throughput sequencing. Our findings could provide a valuable basis for further studies on the regulatory roles of miRNAs related to the different immune responses caused by EV71 and CA16 infections.